2016
DOI: 10.3892/etm.2016.3227
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223 promotes mast cell apoptosis by targeting the insulin-like growth factor 1 receptor

Abstract: The present study aimed to examine the functional role of miR-223 in the regulation of mast cell apoptosis. Overexpressed miR-223 in mast cells transfected by Lipofectamine 2000 was used as a model, and miR-223 was found to promote mast cell apoptosis. To investigate the underlying mechanisms involved, the potential and putative target molecules of miR-223 were detected by bioinformatical analysis using predictive software, and western blotting. Insulin-like growth factor-1 receptor (IGF-1R) was found to be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…As the PI3K conformation changes, Ser473 and Thr308 phosphorylation is required for Akt activation (21). A number of previous studies have demonstrated that the PI3K/Akt signaling pathway participated in the regulation of miRNAs on MC degranulation (22)(23)(24). miR-155 controlled MC activation by modulating the PI3Kγ signaling pathway and anaphylaxis in mice with cutaneous anaphylaxis (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the PI3K conformation changes, Ser473 and Thr308 phosphorylation is required for Akt activation (21). A number of previous studies have demonstrated that the PI3K/Akt signaling pathway participated in the regulation of miRNAs on MC degranulation (22)(23)(24). miR-155 controlled MC activation by modulating the PI3Kγ signaling pathway and anaphylaxis in mice with cutaneous anaphylaxis (22).…”
Section: Discussionmentioning
confidence: 99%
“…miR-155 controlled MC activation by modulating the PI3Kγ signaling pathway and anaphylaxis in mice with cutaneous anaphylaxis (22). Downregulation of miR-223 promoted MC degranulation via the PI3K/Akt pathway by targeting insulin-like growth factor 1 receptor (23). Lentiviral short hairpin RNA against KCa3.1 inhibited the allergic response in allergic rhinitis and suppressed MCs activity via the PI3K/AKT signaling pathway (24).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of PI3K/Akt signaling in mast cells has previously been investigated (22,23), as has the association between miR expression and PI3K/Akt signaling in mast cell degranulation (24,25). Although miR-223 expression was upregulated in IgE-mediated mast cells, miR-223 downregulation was demonstrated to promote mast cell degranulation and apoptosis via the PI3K/Akt pathway by targeting insulin-like growth factor 1 receptor in mast cells (25,26). Helicobacter pylori neutrophil-activating protein induced the release of histamine and interleukin-6 in human mast cell line-1 via the G protein-mediated mitogen-activated protein kinase (MAPK) and PI3K/Akt pathways (27).…”
Section: Discussionmentioning
confidence: 99%
“…35 miRNA-223 is significantly involved in neoplastic cell development by targeting oncogene BCL-2 and the insulin growth factor 1 receptor (IGF-1R). 40 To the best of our knowledge, the complex network of miRNAs that play major roles in hematopoietic niche microenvironment homeostasis has not been assessed so far in the context of HSC transplantation. The aim of this study was to evaluate the miRNAs involved in angiogenesis, hematopoiesis, and homing of HSC in autologous transplantation setting.…”
Section: Mirna-223mentioning
confidence: 99%
“…In hematological malignancies, miRNA‐223 in bone marrow seems to be a tumor‐suppressive molecule . miRNA‐223 is significantly involved in neoplastic cell development by targeting oncogene BCL‐2 and the insulin growth factor 1 receptor (IGF‐1R) …”
Section: Introductionmentioning
confidence: 99%